Characterization of adult heart rate responses during recreational skateboarding at community skateparks - Wiles, T.; Kellogg, D.; Furr, H.; Nessler, J. A.; Newcomer, S. C. (International Journal of Exercise Science, 2020)
Youth participating in recreational skating at community skate parks attain exercise intensities and durations that are comparable with the CDC's exercise recommendations for cardiovascular fitness for their age group. However, it is currently unclear if adults who skateboard in the same environment also achieve the recommended intensities and durations for cardiovascular fitness. Therefore, the purpose of this study was to test the hypothesis that skateboarding would elicit heart rates and durations consistent with the CDC's recommendations for cardiovascular fitness in adults. Fifty-five subjects between ages 18-55 were recruited from six community skateparks for this study. Subjects completed a questionnaire and were instrumented with a Polar V800 heart rate receiver on the left wrist and an H7 Bluetooth heart rate transmitter around the chest below the pectoralis major. Participants were instructed to engage in a typical skateboarding session on their own board with the duration and intensity of activity to be determined by the participant. The mean age of the participants was 27.4 ± 8.5 years, and participants reported skateboarding at a community skate park a mean of 3.1 ± 1.8 days/week. Participants had a mean heart rate of 138.2 ± 21.9 beats per minute (71.7% of age predicted maximum), skated for 65.5 ± 36.2 minutes, and traveled 4.56 ± 4.5 kilometers. Subjects spent 70% of their total duration at moderate-intensity or above and 30% within the low, and below low-intensity range. Results from this study suggest that adults participating in recreational skateboarding in community skateparks achieve the CDC's exercise recommendations for cardiovascular fitness. These findings may have implications for community skatepark design and professional training programs for adult skateboarding athletes.